Ventral extra-striate cortical areas are required for human visual texture segmentation - Allen, Harriet A.; Humphreys, Glyn W.; Colin, Jessica; Neumann, Heiko (Association for Research in Vision and Ophthalmology, 2009)
A patient (HJA) with bilateral occipital lobe damage to ventral cortical areas V2, V3 and V4 was tested on a texture segmentation task involving texture bar detection in an array of oriented lines. Performance detecting a target shape was assessed as the orientations of the background lines had increasing orientation noise. Control participants found the task easier when the background lines had the same orientation or only slightly shifted in orientation. HJA was poor with all backgrounds but particularly so when the background lines had the same or almost the same orientations. The results suggest that V1 alone is not sufficient to perform easy texture segmentation, even when the background of the display is a homogeneous texture. Ventral extra-striate cortical areas are needed in order to detect texture boundaries. We suggest that extra-striate visual areas enhance the borders between the target and background, while also playing a role in reducing the signal from homogeneous texture backgrounds.